2016
DOI: 10.1371/journal.pgen.1005779
|View full text |Cite
|
Sign up to set email alerts
|

MPV17 Loss Causes Deoxynucleotide Insufficiency and Slow DNA Replication in Mitochondria

Abstract: MPV17 is a mitochondrial inner membrane protein whose dysfunction causes mitochondrial DNA abnormalities and disease by an unknown mechanism. Perturbations of deoxynucleoside triphosphate (dNTP) pools are a recognized cause of mitochondrial genomic instability; therefore, we determined DNA copy number and dNTP levels in mitochondria of two models of MPV17 deficiency. In Mpv17 ablated mice, liver mitochondria showed substantial decreases in the levels of dGTP and dTTP and severe mitochondrial DNA depletion, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 69 publications
5
64
1
Order By: Relevance
“…Study of fibroblasts obtained from individuals with MPV17 deficiency showed similar results with decreased mitochondrial deoxynucleotides and mtDNA depletion. Additionally, the mtDNA loss in these fibroblasts was prevented and rescued by deoxynucleoside supplementation (Dalla Rosa et al., ). This study established deoxynucleotide insufficiency in the mitochondria as the cause of mtDNA depletion in MPV17 deficiency (Dalla Rosa et al., ).…”
Section: Mpv17 Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of fibroblasts obtained from individuals with MPV17 deficiency showed similar results with decreased mitochondrial deoxynucleotides and mtDNA depletion. Additionally, the mtDNA loss in these fibroblasts was prevented and rescued by deoxynucleoside supplementation (Dalla Rosa et al., ). This study established deoxynucleotide insufficiency in the mitochondria as the cause of mtDNA depletion in MPV17 deficiency (Dalla Rosa et al., ).…”
Section: Mpv17 Structure and Functionmentioning
confidence: 99%
“…Studying mitochondria from Mpv17 deficient mice liver and fibroblasts obtained from individuals with MPV17 deficiency showed decreased mitochondrial nucleotides and severe mtDNA depletion. Interestingly, nucleoside supplementation to these fibroblasts was able to prevent and rescue the mtDNA loss; therefore, nucleoside supplementation can be a potential therapeutic strategy for MPV17 ‐related mtDNA maintenance defect (Dalla Rosa et al., ).…”
Section: Managementmentioning
confidence: 99%
“…For instance, fibroblasts from patients with defects in mitochondrial dNTP metabolism show altered frequencies of the individual rNMPs . Furthermore, mice defective in the mitochondrial inner membrane protein MPV17 that is implicated in mitochondrial disease exhibit decreased dGTP and dTTP pools in the liver and increased frequency of rGMP embedded in mtDNA . However, the correlation between rNTP/dNTP ratios and mtDNA rNMP frequency in mammals might not be as clear‐cut as in budding yeast.…”
Section: Mitochondria Lack Efficient Repair Mechanisms For Single Embmentioning
confidence: 99%
“…dNTPs were extracted from total homogenates or mitochondrial pellets and dNTP pools were measured by the polymerase-based method as described previously. 36 2.10 | Quantitative and qualitative assessments of mtDNA in proliferating and quiescent cells DNA was extracted using DNeasy Blood & Tissue Kit (Qiagen), according to the manufacturer instructions. Quantification of relative mtDNA copy number in proliferating and quiescent cells was performed as described previously.…”
Section: Cytosolic and Mitochondrial Dntp Pool Determinationmentioning
confidence: 99%